Tangible Deficits and Tourist Dissatisfaction: Diagnosing Service Gaps in an Emerging Indonesian Coastal Tourism Village - Cahaya Nugrahani; Abdul Haris; Arif Julianto Sri Nugroho; Tasari; Anis Marjukah; M Pujo Darmo; Syska Lady Sulistyowatie (Institut Pariwisata dan Bisnis Internasional, 2025)
Community-based tourism (CBT) is promoted across Indonesia as a vehicle for rural economic revitalization and post-pandemic recovery. Yet, its success hinges on service quality—a dimension often overlooked in emerging destinations. This study employs the SERVQUAL model to assess the service quality gap at Jatimalang Beach Tourism Village, Purworejo Regency, Central Java. A purposive sample of 108 domestic and international tourists completed a structured survey measuring expectations and perceptions across five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Findings reveal a significant overall negative gap (M = –87.27), with tangibles exhibiting the largest deficit (M = –145.50), followed by reliability (–94.12) and empathy (–88.36). Results indicate systemic service underperformance, driven primarily by inadequate physical infrastructure. The study concludes that CBT initiatives lacking investment in tangible assets risk failing to meet tourist expectations, undermining sustainability and competitiveness. Strategic recommendations include prioritizing infrastructure upgrades and service training to align with post-pandemic tourist demands for safety, hygiene, and authenticity.